Responses of international law at the transformation of the asylum system in Europe - Gil Bazo, María Teresa (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The Member States of the European Union are currently facing one of the major challenges or our time. The influx of immigrants towards Europe in a moment of generalised crisis (economical, political an social) gives rise to new problems an questions that need to be solved with a long-term approach that will respect democratic values and human rights. Within this framework, the process of European integration requires that cooperation on immigration issues shall become an urgent matter, dealt with by Member States of the European Union at the international level. This moment of restrictive transformations in the European International context on immigration and asylum urges reflection on the status of the right of asylum in International Law. Such status is not only defined by the specific instruments relating to the protection of refugees, but also by other Isnternational instruments for the protection of human rigths,and by International Customary law itself. This is an approach ofen forgottes, whose relevance increases before the always stronger restrictions imposed on the specific asylum regime by European States. Therefore, this article aims at analysing International Refugee Law and the way in which it may be enhanced by International Human Rights Law in order to provide amswers to the modifications introduced in the European legislations.